ANTIMICROBIAL, INSECTICIDAL, AND ANTIRADICAL ACTIVITY OF SOLANUM VIRGINIANUM L. (SOLANACEAE) - Tr, Prashith Kekuda; Hl, Raghavendra; Mr, Rajesh; Hc, Avinash; Gn, Ankith; Kn, Karthik (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objectives: The present study was conducted to determine antimicrobial, antiradical, and insecticidal activity of methanolic extract of the whole plant of Solanum virginianum L. (Solanaceae). Methods: Extraction of shade dried and powdered plant material was carried out by maceration process. Antibacterial and antifungal activities of extract were determined by agar well diffusion and poisoned food technique, respectively. Antiradical activity of extract was assessed by 1,1-diphenyl- 2-picrylhydrazyl (DPPH) and 2,2-azinobis 3-ethylbenzothiazoline 6-sulfonate (ABTS) free radical scavenging assays. Insecticidal activity, in terms of larvicidal activity, was evaluated against 2nd and 3rd instar larvae of Aedes aegypti. Results: The extract exhibited inhibitory activity against all bacteria. Gram-positive bacteria showed greater susceptibility to extract when compared to Gram-negative bacteria. The extract was effective in inhibiting the mycelial growth of all test fungi with marked activity against Curvularia sp. and Alternaria sp. The extract scavenged DPPH and ABTS radicals dose dependently with an inhibitory concentration value of 45.66 and 7.37Î¼g/ml, respectively. The extract showed concentration-dependent larvicidal activity with high lethal activity observed against 2nd instar larvae with lethal concentration value of 0.82 mg/ml. Conclusion: In suitable form, the plant can be used as an effective agent against microbial infections and oxidative damage and to control insect vectors which transmit several diseases.